2001
DOI: 10.1063/1.1390308
|View full text |Cite
|
Sign up to set email alerts
|

High temperature x-ray diffraction studies on antiferroelectric and ferroelectric phase transitions in (Pb1−xBax)ZrO3 (x=0.05,0.10)

Abstract: We have carried out high temperature x-ray diffraction studies on (Pb1−xBax)ZrO3(PBZ) to correlate the large thermal hysteresis (∼100 °C for x=0.05) and irreversibility (for x=0.10) of the antiferroelectric (AFE)–ferroelectric (FE) phase transition observed in dielectric measurements with structural changes. It is shown that for both the compositions, the sequence of phase transitions during heating is orthorhombic antiferroelectric (AO) to rhombohedral ferroelectric (FR) and then to cubic paraelectric (PC). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Following the same procedure, 31 we have observed that the ratio of the intensities of (004) O and (240) We have further plotted the peak intensities ratio (004)/ (240) O extracted from these graphs as a function of x in Fig. 3(b).…”
Section: A Structural Resultsmentioning
confidence: 87%
“…Following the same procedure, 31 we have observed that the ratio of the intensities of (004) O and (240) We have further plotted the peak intensities ratio (004)/ (240) O extracted from these graphs as a function of x in Fig. 3(b).…”
Section: A Structural Resultsmentioning
confidence: 87%
“…Hence, for studying the phases coexistence region at the FEeAFE border, we have concentrated on the influence of La 3þ addition on intensities evolution of (10 0) and (111) reflections [25]. The (10 0) reflection appears as a singlet and well split doublet in the XRD patterns for the FE and AFE phases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In PBZ, the AFE and FE phases were characterized as orthorhombic and rhombohedral structure, respectively. It is reported that the AFE→FE phase transition produces a large increase in volume [5]. Furthermore, the electric-field required to induce AFE→FE switching is much lower than for PbZrO 3 (PZ) which has created interest in PBZ for potential use in large displacement actuator devices requiring low switching voltages [8].…”
Section: Introductionmentioning
confidence: 99%
“…Later on, many authors have investigated the properties of PBZ, especially its phase transitions [1][2][3][4][5][6][7]. Shirane [3] was one of who first demonstrated the antiferroelectric to ferroelectric (AFE→FE) phase transition in PBZ solid solution compositions with x ≥ 0.05.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation